1990
DOI: 10.1148/radiology.177.3.2243966
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland: plain and gadolinium-enhanced MR imaging.

Abstract: The purpose of this study was to show the typical appearance of lesions of the parotid gland with plain MR imaging and MR imaging enhanced with gadopentetate dimeglumine. Seventeen patients with inflammatory changes and 43 with benign and malignant tumors were studied. The examinations were carried out with plain T1-weighted sequences with a repetition time (TR) of 500 msec and an echo time (TE) of 25 msec (TR/TE = 500/25), T2-weighted sequences (1,600/90), and gadolinium-enhanced T1-weighted sequences in axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
3
4

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 0 publications
1
27
3
4
Order By: Relevance
“…A similar tendency of increased signal intensity on T 2 weighted images in lowergrade malignancies was reported for adenoid cystic carcinomas of the head and neck region [10]. In contrast with the previous literature that describes ill-defined margins on MR images as a predictor of high-grade malignancies [6][7][8][9], half of our low-grade MECs had illdefined margins on MR images, reflecting peritumoural inflammatory changes. This peritumoural reactive inflammation in low-grade MECs has also been described in the pathology literature [2,11]; however, our study is the first to present this radiologically.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…A similar tendency of increased signal intensity on T 2 weighted images in lowergrade malignancies was reported for adenoid cystic carcinomas of the head and neck region [10]. In contrast with the previous literature that describes ill-defined margins on MR images as a predictor of high-grade malignancies [6][7][8][9], half of our low-grade MECs had illdefined margins on MR images, reflecting peritumoural inflammatory changes. This peritumoural reactive inflammation in low-grade MECs has also been described in the pathology literature [2,11]; however, our study is the first to present this radiologically.…”
Section: Resultssupporting
confidence: 82%
“…This peritumoural reactive inflammation in low-grade MECs has also been described in the pathology literature [2,11]; however, our study is the first to present this radiologically. This may be because previous studies of MECs included only a small number of patients with low-grade MECs, ranging from one to four patients per study [6][7][8][9]. In contrast, our study is the first to radiologically evaluate more than ten cases of low-grade MECs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, MR images were not specific in differentiation of adenocystic carcinomas from other types of tumors (Sigal et al 1992). It has been suggested that highly malignant parotid tumors are characterized by unsharp margins (Vogl et al 1990) and low signal intensity on both T1-and T2-weighted images Biller 1989, Takashima et al 1997). The authors suggested that in high-grade malignancies of parotid gland the cellularity and relative lack of free water and mobile protons produced a low T2-weighted signal.…”
Section: Tissue Characterization In Head and Neck Tumor Imagingmentioning
confidence: 99%
“…This va lu e was sig ni fi cantly hig her than the ot her tu mors. Ade noma to us tu mors may ha ve very high ADC va lu es beca u se of the flu id con ta i ning are as as al so pre vi o usly re por ted by Vogl et al 14 Mo re o ver, this va lu e is clo se to the thres hold va lu e (2.1 x 10 -3 mm 2 /sec) that was de ter mi ned by Sa ka mo to et al 15 for cystic le si ons. In the light of this in for ma ti on, we con si de red that ca na li cu lar ade no mas had high ADC va lu es du e to the ir ade no ma to us struc tu re.…”
Section: Discussionmentioning
confidence: 77%